Studies towards the first synthesis of Tetronothiodin - Olivier Dubert (2005)
In our studies towards the synthesis of tetronothiodin, we completed the synthesis of 195, a precursor of the oxaspirobyciclic unit of tetronothiodin. The synthesis was achieved in an eight step strategy and afforded the α-hydroxy lactone 195 as a diasteroisomeric mixture with 194 in a 5.7% overall yield.....